Factores relacionados con el estrés postraumático en pacientes con alta médica por la COVID-19 - Rioja Castañeda, Miguel Eduardo (2022)
Introduction: Hospitalization due to COVID-19 can predispose to the appearance of possible long-term psychological sequelae. Objective: To determine the relationship between hospital and non-hospital factors with post-traumatic stress in patients discharged for COVID-19 from a hospital in Peru. Methods: Cross-sectional study and correlational design. The non-probabilistic sample consisted of 126 participants, evaluated through a self-administered questionnaire and the Davidson Trauma Scale. For data processing, the chi-square test and Cramer's V were used as measures of the magnitude of effect. Results: Post-traumatic stress disorder presents moderate associations with hospital factors: hospitalization time (p<0.001) (Cramer's V = 0.33), clinical type of COVID-19 (p<0.001) (Cramer's V = 0 .49) and invasive ventilatory support (p<0.001) (Cramer's V = 0.39); and with non-hospital factors: oxygen therapy in rehabilitation (p<0.001) (Cramer's V = 0.33), neurological sequelae (p<0.001) (Cramer's V = 0.41), respiratory distress (p<0.001) (Cramer's V = 0.53), perception of social discrimination (p<0.05) (Cramer's V = 0.29), difficulty returning to daily activities (p<0.001) (Cramer's V = 0.40) and family members infected with COVID-19 (p<0.001) (Cramer's V = 0.30). Conclusions: There are both in-hospital and out-of-hospital factors associated with post-traumatic stress disorder following discharge from COVID-19.